Scaling of strength reduction factors for degrading elasto-plastic oscillators. - Chakraborti, Arindam (Earthquake engineering & structural dynamics.)
The inelastic (design) spectra characterizing a seismic hazard are generally obtained by the scaling-down of the elastic (design) spectra via a set of response modification factors. The component of these factors, which accounts for the ductility demand ratio, is known as the strength reduction factor (SRF), and the variation of this factor with initial period of the oscillator is called an SRF spectrum. This study considers scaling of the SRF spectrum in the case of an elasto-plastic oscillator with strength and stiffness degradation characteristics. Two models are considered : one depending directly on the chracterization of source and site parameters and the other depending on the normalized design spectrum characterization of the seismic hazard. The first model is the same as that proposed earlier by the second author, and is given in terms of earthquake magnitude, strong-motion duration, predominant period, geological site conditions, ductility demand ratio and ductility supply related parameter. The second model is a new model proposed here in terms of the normalized pseudo spectral acceleration values (to unit peak ground acceleration), ductility demand ratio and ductility supply-related parameter. For each of these models, least square estimates of the coefficients are obtained through regression analyses of the data for 956 recorded accelerograms in western USA. Parametric studies carried out with the help of these models confirm the dependence of SRF's on strong motion duration and earthquake magnitude besides predominant period and site conditions. It is also seen that degradation characteristics make a slight difference for high ductility demands and may lead to lower values of SRFs, unless the oscillators are very flexible.